SETS, Arbitrage Activity, and Stock Price Dynamics - Nick Taylor; Dick van Dijk; Philip Hans Franses; André Lucas (Tinbergen Institute, 1999)
This paper provides an empirical description of the relationshipbetween the trading system operated by a stockexchange and the transaction costs faced by heterogeneous investors who use the exchange. Therecent introduction ofSETS in the London Stock Exchange provides an excellent opportunity tostudy the impact of an electronic trading systemupon transaction costs and the time taken to carry out a trade. Using thecost-of-carry model of futures prices we estimate(non-linearly) the transaction costs and trade speeds faced by arbitragerswho take advantage of mispricing of FTSE100futures contracts relative to the spot prices of the stocks that make upthe FTSE100 stock index. We divide the sample periodinto pre-SETS and post-SETS sample periods and conduct a comparative studyof arbitrager behaviour under differenttrading systems. The results indicate that there has been a significantreduction in the level of transaction costs faced byarbitragers and in the degree of transaction cost heterogeneity since theintroduction of SETS. Finally, generalised impulseresponse functions show that both spot and futures prices adjust morequickly in the post-SETS period.
Keywords: 330; Börse; Computerunterstützung; Arbitrage; Börsenkurs; Transaktionskosten; Theorie; Großbritannien